Stereocontrolled Radical Bicyclizations of Oxygenated Precursors Enable Short Syntheses of Oxidized Abietane Diterpenoids - Vrubliauskas, Darius; Gross, Benjamin M; Vanderwal, Christopher D (Journal of the American Chemical Society, 2021)
The power of cation-initiated cyclizations of polyenes for the synthesis of polycyclic terpenoids cannot be overstated. However, a major limitation is the intolerance of many relevant reaction conditions toward the inclusion in the substrate of polar functionality, particularly in unprotected form. Radical polycyclizations are important alternatives to bioinspired cationic variants, in part owing to the range of possible initiation strategies, and in part for the functional group tolerance of radical reactions. In this article, we demonstrate that Co-catalyzed MHAT-initiated radical bicyclizations are not only tolerant of oxidation at virtually every position in the substrate, oftentimes in unprotected form, but these functional groups can also contribute to high levels of stereochemical control in these complexity-generating transformations. Specifically, we show the effects of protected or unprotected hydroxy groups at six different positions and their impact on stereoselectivity. Further, we show how multiply oxidized substrates perform in these reactions, and finally, we document the utility of these reactions in the synthesis of three aromatic abietane diterpenoids.